The human being: constructor of symbols - Jaramillo Mejía, Rosemberg (Rastros Rostros, 2023)
Symbols in general are those that allow cognition and the designation of things, of which it is possible to make reference in communication. They are the form of representation of everything that is produced in thought, either as an apprehension of the external world, or as a product of fantasy or cultural creation, or as an elaboration in terms of the construction of knowledge, of affective and volitional organization or of social interaction.